HIDRADENITIS SUPPURATIVA - A CASE REPORT - MI, Nnamonu (West African College of Surgeons, 2011)
Hidradenitis suppurativa is a chronic and disfiguring skin disease characterized by multiple abscesses and sinuses. Often it is not recognized early in this environment as a result of limited awareness of this condition. The author sought to review available knowledge on this condition and report a case currently being managed in a general surgery unit. Literature search was conducted using the Google search engine and a patient who presented to the author’s unit is presented. In conclusion, hidradenitis suppurativa is a distressing disease. High index of suspicion and relevant investigations would improve early diagnosis; several options are available for treatment with good outcome depending on the stage of the disease.